Floristic inventory of the gallery forest of the Metztitlán river, Hidalgo, Mexico - Mendoza Cariño, Mayra; Quevedo Nolasco, Abel (Instituto de Ecología, A.C., 2019)
Background and Aims: The gallery forest (GF) of the Metztitlán river is ecologically important within the Barranca de Metztitlán Biosphere Reserve and contributes to the sustainability of biodiversity and the development of numerous biological processes. The objectives of this study were to create a floristic inventory of the GF in the Reserve, and to determine the composition of native and exotic species, their distribution capacity, habitat and risk status according to the NOM-059-SEMARNAT-2010 and the Red List of Endangered Species (IUCN).Methods: Botanical collections were carried out in the rainy (2013) and dry (2014) seasons on both sides of the river. Taxonomic identification was based on the Phanerogamic Flora of the Valley of Mexico and the Flora of the Bajío and adjacent regions, confirmed by specialists and in the Herbarium-Hortorio (CHAPA) of Colegio de Postgraduados. Through bibliographical revisions, we determined the distribution capacity of the species, their habitat and risk status (NOM-059-SEMARNAT-2010 and IUCN).Key results: We identified 122 species of vascular plants belonging to 38 families and 102 genera. The most representative families were Asteraceae (21 genera and 24 species) and Poaceae (12 and 17); the genera with the highest number of species were Cyperus (4) and Eragrostis (4). Of the total species, 81 are native, five of them probably native to Mexico; 34 are exotic, one from unknown origin; and three are endemic to Mexico. None of the taxa was found to be in a risk status.Conclusions: The GF in the Barranca de Metztitlán Biosphere Reserve shows anthropic alterations that favor the establishment of exotic species, which make up 27% of the floristic inventory and predominance in plant cover.